Stroock–Varadhan Theorem for Flows Generated by Stochastic Differential Equations with Interaction - Pilipenko, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove a theorem that characterizes the support of a flow generated by a system of stochastic differential equations with interaction.